The relative age-related participation trends in European Badminton - MERT BILGIC; ERHAN DEVRILMEZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: T he purpose of this study was to identify the relative age effect (RAE) in European youth badminton through examining participation trends. Material and methods: T he birthdate distributions of 1909 badminton players (males = 994, females = 915) participating in the last three consecutive European U15, U17 and Junior (U19) Badminton Championships were analysed. Chi-square (χ²) goodness-of-fit tests were used to determine inter-quartile differences, and odds ratios (OR) and 95% confidence intervals were calculated in order to compare quartiles with each other. Results: Statistically significant over-representation of players born shortly after the cut-off date was determined. Regarding gender, RAE was more notable in males compared to females, and the strongest results were determined in U15 compared to the other age categories. Moreover, striking trends were determined in Q1-Q4 comparisons, particularly as players in Q1 were more than twice for females and thrice for males as likely to participate in the European Badminton Championships. Conclusions: F indings of this study confirm the presence of RAE in European youth badminton though decreasing its intensity with age. Certain precautions or different approaches should be taken into consideration to organize the age categories, such as biological markers, variations, rotations or age quota for equal opportunities.